Penerapan Diversi melalui Pendekatan Keadilan Restoratif (Restorative Justice) pada Anak Pelaku Penyalahgunaan Narkotika - Putu Ayu Sarina Selsa Oktaviani; Anak Agung Sagung Laksmi Dewi; I Nyoman Gede Sugiartha (Jurnal Preferensi Hukum, 2021)
This research aims to find out how implementation of the diversion of the perpetrators of the abuse of narcotic drugs by using the method of the approach of restorative justice by involving the perpetrator, the victim, the family of the offender or the victim, community counselors and professionals. The research method used is the normative legal research with approach of legislation, articles as well as the doctrine or the views from experts associated with the diversion and narcotic in children. With regard to the handling of child abuse of narcotic drugs, the problems in this thesis is the arrangement of diversion by law about the criminal justice system of the child and the application of diversion through approach restorative justice in the criminal offence of child perpetrator of abuse of narcotic. The settings regarding diversion here is actually a settling criminal acts with children outside of the criminal justice process. Where the diversion can be carried out against the perpetrator of the crime that the threat of punishment of less than 7 (seven) years and is not a repetition of the crime. Against the application of the abuse of narcotics diversion for children conducted through deliberation in accordance whit the provisions of article 8 of law about the criminal justice system so that children can make a deal with diversion consider the child’s interests, in this case intended to avoid and keep children from the judicial process. In terms of the results of the diversion agreement already agreed upon with the parties where the implementation of the outcome of the diversion agreement would of course also have to be monitored both from the elderly, the environment, and investigators also rehabilitation center to ascertain if the result of the diversion deal was already done by the child and reported to the Chairman of the District Court where the implementation of such diversion is implemented.